2020
DOI: 10.3390/vetsci7040169
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of Bovine Viral Diarrhea Virus Non-Structural NS4B Protein in Viral Pathogenesis

Abstract: Bovine viral diarrhea virus (BVDV) is a (+) ssRNA virus that belongs to the family Flaviviridae. BVDV is a significant animal pathogen causing substantial economic losses to the cattle industry worldwide through respiratory and gastrointestinal infections and abortion or birth of persistently infected calves. While the immunogenic profile of some of the BVDV proteins (i.e., Erns, E2 and NS3) is well established during viral pathogenesis, very little information is available about most of BVDV’s non-structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…NS4B contains highly conserved epitopes and can induce humoral and cellular immune responses after viral infection. To study the immunogenicity of NS4B and identify the specific antibody of BVDV-NS4B, Bashir et al found that cattle were immunized with a combination of NS4B and a modified version of BVDV-1a (NADL strain) [ 70 ]. The presence of BVDV NS4B specific antibodies was detected in the serum of BVDV-immunized cows by immunoblotting and indirect ELISA.…”
Section: Non-structural Proteinsmentioning
confidence: 99%
“…NS4B contains highly conserved epitopes and can induce humoral and cellular immune responses after viral infection. To study the immunogenicity of NS4B and identify the specific antibody of BVDV-NS4B, Bashir et al found that cattle were immunized with a combination of NS4B and a modified version of BVDV-1a (NADL strain) [ 70 ]. The presence of BVDV NS4B specific antibodies was detected in the serum of BVDV-immunized cows by immunoblotting and indirect ELISA.…”
Section: Non-structural Proteinsmentioning
confidence: 99%